2022
DOI: 10.3390/healthcare10081595
|View full text |Cite
|
Sign up to set email alerts
|

Digital Care Programs for Chronic Hip Pain: A Prospective Longitudinal Cohort Study

Abstract: Chronic hip pain is a cause of disability worldwide. Digital interventions (DI) may promote access while providing proper management. This single-arm interventional study assesses the clinical outcomes and engagement of a completely remote multimodal DI in patients with chronic hip pain. This home-based DI consisted of exercise (with real-time biofeedback), education, and cognitive-behavioral therapy. Outcomes were calculated between baseline and program end, using latent growth curve analysis. Primary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(120 reference statements)
1
3
0
Order By: Relevance
“…In the present study, pain levels reported by both groups at baseline (4.6–4.8 points) were within the range of those described in the literature for CMP both in telerehabilitation (5.8–4.5 points) [ 31 , 32 , 33 , 34 , 52 , 53 , 89 ] and in conventional physical therapy (4.6–5.8 points) studies [ 90 , 91 , 92 ]. When analyzing the impact of telerehabilitation interventions on pain reduction at 1-year, the results varied, possibly depending on a number of factors, including baseline pain severity, type of pain management strategy, length of the intervention and particularly the affected joint (e.g., several anatomic regions (50.9%) [ 31 ], low back (44.8%) [ 93 ], knee (43.9%) [ 32 ], hip (34.5%) [ 32 ], or hip and knee (17.2%) [ 94 ]).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the present study, pain levels reported by both groups at baseline (4.6–4.8 points) were within the range of those described in the literature for CMP both in telerehabilitation (5.8–4.5 points) [ 31 , 32 , 33 , 34 , 52 , 53 , 89 ] and in conventional physical therapy (4.6–5.8 points) studies [ 90 , 91 , 92 ]. When analyzing the impact of telerehabilitation interventions on pain reduction at 1-year, the results varied, possibly depending on a number of factors, including baseline pain severity, type of pain management strategy, length of the intervention and particularly the affected joint (e.g., several anatomic regions (50.9%) [ 31 ], low back (44.8%) [ 93 ], knee (43.9%) [ 32 ], hip (34.5%) [ 32 ], or hip and knee (17.2%) [ 94 ]).…”
Section: Discussionsupporting
confidence: 85%
“…The DCP, previously described elsewhere [ 53 , 54 , 60 ], consisted of an 8 or 12-week program comprising exercise, education and cognitive behavioral therapy (CBT). Upon enrollment each participant was assigned to a PT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations